An evaluation of the SOAR-High Project: a web-based science program for deaf students. - Barman CR; Stockton JD (American Annals of the Deaf, 2002)
The investigators evaluated the SOAR-High (Science, Observing, and Reporting-High School) Project, a web-based earth systems science course involving collaborating teachers and deaf students at high schools in California, Washington, DC, and Indiana. In SOAR-High, students use Internet- and computer-based technologies to gather and report information. The investigators and stakeholders identified 4 key questions: (a) Are the SOAR-High students becoming proficient in using the science process skills? (b) Do the SOAR-High curriculum materials explicitly stress the use of science process skills? (c) Do the SOAR-High students develop skills to work independently? (d) Does the SOAR-High Project aid in student motivation? Quantitative and qualitative evaluative tools to address each question included student and teacher interviews, classroom observations, performance-based tasks, and reviews of student website work. Findings showed convincing evidence for affirmative answers to all 4 questions. However, some students described difficulties with the reading levels of the SOAR-High materials; some teachers expressed concern about SOAR-High's effectiveness because of its use with students at different grade levels.